Regulation of drug resistance and virulence of Acinetobacter baumannii by quorum sensing system under antibiotic pressure - Jiang, Xingyu; Shan, Xuchun; Yang, Xiaomeng; Zhang, Xin; Xiang, Yang; Chen, Yan; Ni, Zhaohui (Frontiers in Microbiology, 2026)
IntroductionAcinetobacter baumannii is a formidable pathogen renowned for its role in hospital-acquired infections. In recent years, largely due to antibiotic abuse and other reasons, bacteria are frequently exposed to sub-minimum inhibitory concentration (sub-MIC) levels of antibiotics. Accumulating evidence suggests that sub-MIC antibiotic pressure serves as a critical driver of bacterial resistance evolution and virulence adaptation. However, the regulatory mechanisms underlying antibiotic stress adaptation in A. baumannii remains poorly understood. The quorum sensing (QS) system is a key bacterial signaling network that senses population density and coordinates vital physiological functions and environmental adaptations. Targeting QS system to attenuate virulence and resistance represents a promising strategy for combating multi-drug-resistant infections. Nevertheless, the role of systems in regulating antibiotic stress response in A. baumannii has not been elucidated.MethodsIn this study, we used the wild-type (WT) strain of A. baumannii and an isogenic abaI deletion mutant strain (ΔabaI) to investigate the involvement of QS in adaptive responses under meropenem sub-MIC pressure. The analysis was performed by phenotypic experiments such as bacterial biofilm formation and motility detection, transcriptome sequencing (RNA-seq) and qRT-PCR verification.ResultsWe found that under antibiotic pressure, the WT strain developed significantly enhanced resistance, accompanied by increased biofilm formation, surface motility, adherence to and invasion of A549 cells, and pathogenicity in Galleria mellonella. In contrast, the ΔabaI strain showed no significant changes in resistance, motility, host cell adhesion and invasion, or virulence, with all these parameters remaining substantially lower than those of the antibiotic-treated WT. Interestingly, biofilm formation was still significantly enhanced in the ΔabaI strain, suggesting compensatory activation of alternative regulatory mechanisms. Transcriptomic analysis revealed that sub-MIC meropenem triggered extensive gene expression changes in both the WT and ΔabaI strains. In the WT, differentially expressed genes were enriched in pathways including quorum sensing, biofilm formation, ABC transporters, and two-component systems. In contrast, the ΔabaI mutant exhibited distinct transcriptional profiles, with enrichment in Δ-lactam resistance, aromatic amino acid biosynthesis, and metabolite transport. The expression trends of key virulence- and resistance-associated genes were further validated by qRT-PCR, confirming the reliability of the RNA-seq data.DiscussionOur study underscores the potential of targeting the QS system to mitigate antibiotic-driven adaptation and provides a strategic basis for controlling multidrug-resistant A. baumannii infections.